Usefulness of non–contrast‐enhanced MRI with two‐dimensional balanced steady‐state free precession for the acquisition of the pulmonary venous and left atrial anatomy pre catheter ablation of atrial fibrillation: Comparison with contrast enhanced CT in clinical cases. Issue 2 (7th July 2015) - Shigenaga, Yutaka; Okajima, Katsunori; Ikeuchi, Kazushi; Kiuchi, Kunihiko; Ikeda, Takayuki; Shimane, Akira; Yokoi, Kiminobu; Teranishi, Jin; Aoki, Kousuke; Chimura, Misato; Yamada, Shinichiro; Taniguchi, Yasuyo; et al.
Abstract : Background: To investigate the feasibility of substituting non–contrast‐enhanced MR (non–CE‐MR) imaging with a two‐dimensional (2D) balanced steady‐state free precession (b‐SSFP) sequence for contrast‐enhanced computed tomography (CE‐CT) for atrial fibrillation (AF) ablation. Methods: Fifty‐four patients that underwent AF ablation under the guidance of a 3D electro‐anatomical mapping system with CE‐CT (n = 27) or non–CE‐MR images (n = 27) were studied. Procedural results were compared between the two groups. Furthermore, in 22 patients who underwent both CE‐CT and non–CE‐MRI, two cardiologists independently scored the multiplanar reformatted images on a scale of 1 to 4 (from 1, poor, to 4, excellent). Results: The image score was nearly 0.5 point higher with the CE‐CT method. However, the procedural results such as the surface registration error (1.0 [0.8–1.6] mm versus 1.0 [0.8–1.35] mm, P = 0.88) and procedure time (185 [159–199] min versus 185 [142–221] min, P = 0.86) did not significantly differ between the CE‐CT and non–CE‐MR groups. Conclusion: The non–CE‐MR method with a 2D‐b‐SSFP sequence can give us adequate information on AF ablation without any radiation exposure or contrast medium usage. J. Magn. Reson. Imaging 2016;43:495–503.